2020
DOI: 10.1159/000511263
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Screen Time, and Sleep Duration of Children Aged 6–9 Years in 25 Countries: An Analysis within the WHO European Childhood Obesity Surveillance Initiative (COSI) 2015–2017

Abstract: <b><i>Background:</i></b> Children are becoming less physically active as opportunities for safe active play, recreational activities, and active transport decrease. At the same time, sedentary screen-based activities both during school and leisure time are increasing. <b><i>Objectives:</i></b> This study aimed to evaluate physical activity (PA), screen time, and sleep duration of girls and boys aged 6–9 years in Europe using data from the WHO European Childhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
77
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 36 publications
9
77
0
5
Order By: Relevance
“…It shows that physically active children had less anxiety, worry, nervousness, and sensitive behavior during the pandemic. This finding is consistent with previous research indicating that PA reduces, among other things, anxiety and the risk of obesity and early metabolic risk factors (24)(25)(26)(27). Additionally, during childhood, PA levels tend to impact adolescence and adulthood, which is another reason for regular PA in childhood (24,28).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…It shows that physically active children had less anxiety, worry, nervousness, and sensitive behavior during the pandemic. This finding is consistent with previous research indicating that PA reduces, among other things, anxiety and the risk of obesity and early metabolic risk factors (24)(25)(26)(27). Additionally, during childhood, PA levels tend to impact adolescence and adulthood, which is another reason for regular PA in childhood (24,28).…”
Section: Resultssupporting
confidence: 92%
“…This finding is consistent with previous research indicating that PA reduces, among other things, anxiety and the risk of obesity and early metabolic risk factors (24)(25)(26)(27). Additionally, during childhood, PA levels tend to impact adolescence and adulthood, which is another reason for regular PA in childhood (24,28). School achievement directly affected the variable study time, showing that better students spent more time studying or searching for study materials during the EM.…”
Section: Resultssupporting
confidence: 91%
“…In a study with 16 countries published in 2015 (Shaw et al 2015), Portugal ranked in 14th place, along with Italy and just before South Africa, as the countries with less independent mobility. More recently, results from the WHO Childhood Obesity Surveillance Initiative (COSI), which provide an overview of the PA habits of children in the WHO European Region, showed that Portuguese children were the ones with the lowest levels of active travel to school (Whiting et al 2020). Conversely, although most Portuguese children spent about 1 h a day watching TV or using electronic devices, their levels of screen time involvement were not as high as in most other countries (Whiting et al 2020).…”
mentioning
confidence: 99%
“…Numerous studies have examined the relationship between time spent on passive entertainment such as television, mobile telephones, or video games and the presence of or predisposition to childhood and adolescent obesity [36][37][38][39][40][41][42][43][44][45]. However, few studies have been conducted on screen time and its association with eating patterns [46][47][48].…”
Section: Discussionmentioning
confidence: 99%